Ke arah pembentukan kurikulum pendidikan seni sekolah menengah berorientasikan teknologi maklumat - Mohd Zahuri, Bin Khairani (Universiti Malaysia Sarawak (UNIMAS), 2002)
This research is carried out towards the implementation of computer literacy the Art syllabus for Form 4 and 5 students. With the development of the post modern in the field of information technology it has become crucial for education to be dominated by computer technology. To achieve this aim, a survey has been carried out among art teachers to gauge their level of computer knowledge. Questions, which cover the study of attitudes, relationships, knowledge, responsibility and teachers' efforts toward computer knowledge, have been analysed using the descriptive method. This study also highlights the transformational challenges, beginning with the traditional educational approaches to that which employ the computer